2018
DOI: 10.1016/j.celrep.2018.05.094
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the Localization of Sperm-Retained Histones Revealed the Modification-Dependent Accumulation in Specific Genome Regions

Abstract: The question of whether retained histones in the sperm genome localize to gene-coding regions or gene deserts has been debated for years. Previous contradictory observations are likely caused by the non-uniform sensitivity of sperm chromatin to micrococcal nuclease (MNase) digestion. Sperm chromatin has a highly condensed but heterogeneous structure and is composed of 90%∼99% protamines and 1%∼10% histones. In this study, we utilized nucleoplasmin (NPM) to improve the solubility of sperm chromatin by removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 37 publications
5
95
0
Order By: Relevance
“…As described above, the distribution of sperm derived histone PTMs on zygotic genome is not random, but follows a specific pattern [209,210]. In detail, sperm retained histones are enriched at development-related loci, including imprinted gene clusters, binding sites of chromatin insulator protein CCCTC-binding factor (CTCF) and promoters of developmental transcription and signaling factors [37,174,182,187,206,211,212].…”
Section: Sperm Histone Ptms: a Potential Role In Embryo Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, the distribution of sperm derived histone PTMs on zygotic genome is not random, but follows a specific pattern [209,210]. In detail, sperm retained histones are enriched at development-related loci, including imprinted gene clusters, binding sites of chromatin insulator protein CCCTC-binding factor (CTCF) and promoters of developmental transcription and signaling factors [37,174,182,187,206,211,212].…”
Section: Sperm Histone Ptms: a Potential Role In Embryo Developmentmentioning
confidence: 99%
“…In detail, sperm retained histones are enriched at development-related loci, including imprinted gene clusters, binding sites of chromatin insulator protein CCCTC-binding factor (CTCF) and promoters of developmental transcription and signaling factors [37,174,182,187,206,211,212]. Most of them have unmethylated CpG-rich promoters and are enriched of H3K4me2/3 or H3K27me3 [111,174,182,194,205,206,209,212,213]. Actually, H3K4me3 marks promoters of microRNA clusters, transcription and signaling factors (i.e., STAT3, KLF4/5, SOX7/9), developmental genes and paternally expressed imprinted genes (i.e., MEST, BEGAIN, DLK1, RTL).…”
Section: Sperm Histone Ptms: a Potential Role In Embryo Developmentmentioning
confidence: 99%
“…In addition, CGIs retain nucleosomes in spermatozoa, foregoing the exchange for protamines [28][29][30] . These retained nucleosomes include canonical H3 or its variant H3.3, which are enriched for di-and/or tri-methylation on lysine 4 (H3K4me2/3) 30,34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found sperm histones enriched next to promoter regions of genes related to embryo development, miRNA, HOX genes, imprinted genes and chromatin binding sites like CCCTC-binding factor (ARPANAHI et al, 2009;BRYKCZYNSKA et al, 2010;. On the opposite side, other studies found nucleosome structures enriched at intergenic regions or gene deserts (SAITOU; YAMAGUCHI et al, 2018). These divergent results may be partially explained due to differences in experimental details and technical process used to map the nucleosome over the sperm DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In this process, it is possible to increase the chances of somatic cells contaminations or immature cells in the sample, which could explain the difference find between species. Recently, ChIP-Seq comparison of mice sperm samples submitted only to swim-up and swim-up and percoll verified some differences between sequencing data suggesting swim-up sperm samples could contain non-sperm cells contamination, which could have impacted the ChIP-seq results (YAMAGUCHI et al, 2018). Then, the sperm process can also be a bias to different results between experiments.…”
Section: Discussionmentioning
confidence: 99%